Consumer preference towards UM Land's brand as houses of choice / Puteri Ili Nur Aliaa Ashaari Azman - Ashaari Azman, Puteri Ili Nur Aliaa (Faculty of Business and Management, 2007)
The purpose of this research is to study the factors that influence UM Land's brand as a developer in becoming a preferred choice which was done in Bangi area. This research will answered three research objectives which are to identify the factors that make UM Land Bhd as brand of choice and to analyze the factors that influenced consumer preference towards brand of choice. Moreover, this research will determined the relationship between factors influencing consumer preference and brand of choice which will answer the third research objective. In this research, questionnaire and interview techniques which are the primary data as well as other secondary data such as company annual reports, journals, reference books, newspaper and internet are used by the researcher to collect data and information. The researcher used non-probability sampling technique where the sample are choose conveniently base on whoever visit the sales gallery and booth in the month of March 2007. Based on reliability testing, frequency and cross tabulation, a clear findings and result are gathered. The findings showed that there are relationships between the factors influencing consumer preference and brand of choice. Besides that, the findings highlight that all the factors in consumer preference influenced the factors in brand of choice. Moreover, from the findings also it shows the factors that make UM Land Bhd as brand of choice and factors that influencing consumer preference towards brand of choice. Furthermore, the researcher is able to give some recommendations and suggestion for UM Land Bhd to take into their consideration for their future planned development.